NECESSARY CONDITIONS AND REQUIREMENTS FOR THE IMPLEMENTATION OF SIMULATION COURSES IN HIGHER EDUCATION - Abdullaev R.N. (Scholar Express Journal, 2022)
The purpose of these studies is to show the most important advantages of modeling technologies. The objectives of our article are to study and learn without harming the patient, and with the help of simulation training methods to assess the achieved high level of professional training of each specialist
Keywords: modeling technologies; simulation training methods